Altering the status quo experiences of the Faculty of Law in the accreditation process may june 2013- 2015 - León Guzmán, Marlen (2015)
Accreditation processes of university careers features a wide space to develop introspection, articulating a complex of formal and substantial requirements, that develops in teaching a career. In the case of the Faculty of Law, this process involved the redefinition of academic work as well as a strong internal reorganization. This allowed to obtain accreditation from the SINAES in June 2015.